PENGARUH KOMITMEN KARYAWAN DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYAWAN PADA KOPERASI CU MANDIRI UNIT DAERAH TEBING TINGGI - Ritonga, Sinar (UNIKA Santo Thomas, 2017)
This study aims to test and analyze Employee Commitment and Communication to Employee Performance at Cooperative CU Mandiri Unit Areas Tebing Tinggi. The data was collected through interviews and questionnaires distributed to 67 employees at CU Mandiri Cooperative Unit of Tebing Tinggi District. Data analysis in this study using SPSS version 20. The technique used is the method of sampling and data testing techniques used in this study include the validity test and reliability test, the classical assumption test. Multiple linear regression analysis, and hypothesis test also conducted to test and prove hypothesis in research. From the result of partial testing (t test) shows tcount (2,240> ttable (1,669) and its significance level is 0,018 ttable (1,669 ) and its significance level is 0.000 Ftable is 46,209> 3,14 and its significance level (0,000